Pick it up as you go along - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Learning and Livelihoods. The experience of the FSIPM project in southern Malawi By A Orr, B Mwale et al, Natural Resources Institute & Government of Malawi, 2000. 58 pp. ISBN 0 85954 524 5 GBP 10 Euro 16.70